2009
DOI: 10.1089/mdr.2009.0868
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of CTX-M-15-ProducingKlebsiella pneumoniaein the Intensive Care Unit of a French Hospital

Abstract: The CTX-M-15 extended spectrum beta-lactamase (ESBL)-producing Klebsiella pneumoniae isolates were identified in 36 patients hospitalized from December 2006 to September 2007 in the medical intensive care unit (ICU) of the Bicêtre hospital, South Paris, France. The incidence of colonization and/or infection was 4.8%. Eighty-nine percent of the ESBL-producing K. pneumoniae isolates were acquired in the ICU, and only 8.3% of the patients were infected. Pulsed field gel electrophoresis (PFGE) analysis of the isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 41 publications
2
14
0
2
Order By: Relevance
“…ESBL-producing, Gram-negative bacilli, mostly Klebsiella pneumoniae but also E. coli, have been increasingly implicated in nosocomial outbreaks in neonatal intensive care units (11,13,15,17). Although many outbreaks have been resolved rapidly by reimplementation of hygiene control measures, there have been some instances where the outbreak was only resolved by temporary ward closure (26,33,35).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ESBL-producing, Gram-negative bacilli, mostly Klebsiella pneumoniae but also E. coli, have been increasingly implicated in nosocomial outbreaks in neonatal intensive care units (11,13,15,17). Although many outbreaks have been resolved rapidly by reimplementation of hygiene control measures, there have been some instances where the outbreak was only resolved by temporary ward closure (26,33,35).…”
Section: Discussionmentioning
confidence: 99%
“…In 2008, Boyer-Mariotte et al reported one case of fatal neonatal meningitis caused by a CTX-M-15-producing E. coli strain (7). Emergence of ESBL-producing Enterobacteriaceae is a major problem, since the choice of drugs for antimicrobial treatment is limited; moreover, such strains have been increasingly implicated in nosocomial outbreaks in neonatal intensive care units (11,23,33,35). While the spread of CTX-M-type ESBL in the family Enterobacteriaceae, especially in E. coli, has been described worldwide (11,13,15,17), the spread of TEM-type ESBL has been less frequently reported (8, 9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic relatedness of the isolates was assessed by pulsed-field gel electrophoresis (PFGE) analysis with XbaI-digested genomic DNA as described previously (16). Multilocus sequence typing (MLST) was carried out with seven standard housekeeping loci (rpoB, gapA, mdh, pgi, phoE, infB, and tonB) according to Diancourt et al (15).…”
Section: Methodsmentioning
confidence: 99%
“…Although stool samples are considered the "gold standard" specimen for studying gut bacteria in general (5,6) and for detecting CRE in particular (7), hospital epidemiologists, clinical microbiologists, and researchers frequently use rectal swabs due to practical considerations, such as ease of collection, handling, and processing (8)(9)(10)(11). Several studies compared the qualitative sensitivity of rectal swabs versus stool specimens for the recovery and detection of various pathogens, such as Campylobacter fetus subsp.…”
mentioning
confidence: 99%